Isolation, identification and antifungal susceptibility of Candida species in postmenopausal women - Abdul Mohsen, Sally; Diyaa Abed Aljaza, (University of Thi-Qar Journal of Science, 2024)
Abstract— The term "vulvovaginal candidiasis" refers to an inflammatory, non-erosive Vulvovaginitis characterized by symptoms such as itching, pain, dyspareunia, and discharge. The condition is treated with antifungal medication if a positive culture from a low vaginal swab reveals Candida. It should be mentioned that these people had ongoing medical conditions. VVC had previously been classified as acute or recurring. It appears that estrogen is a key permissive factor in VVC. Clinical findings have demonstrated that VVC is uncommon in premenopausal and postmenopausal women and that the post-menopausal vagina rarely contains isolated Candida. The study aimed to know the relationship between Vulvovaginitis and candida in postmenopausal women and effectiveness of some antifungals.   A total of 100 postmenopausal women With Vulvovaginitis, aged 45 to 69, had vaginal swabs taken from them. Upon arrival at the laboratory, all samples were cultured on Sabouraud dextrose agar . The species of the isolated yeasts were identified by a variety of methods, including molecular analysis with primers ITS1–ITS4, growth on Chrom agar medium, and biochemical analyses. Result: candida in postmenopausal women  is less than in per menopausal due to effectiveness of estrogen hormone in reproductive age . The outcomes On Chrom agar showed, six species of candida—C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. krusei, and c. rugosa—were isolated. Among the other species, C. glabrata was discovered to be the most prevalent. The findings demonstrated that four species of yeast-like fungi were identified using molecular diagnosis and genetic testing as follows: